Drumming performance and underlying muscle activities in a professional rock drummer with lower-limb dystonia: a case study - Honda, Kazuaki; Sata, Shizuka; Komine, Mizuki; Yamaguchi, Satoshi; Kim, SungHyek; Kashino, Makio; Fujii, Shinya (Frontiers in Neurology, 2024)
Task-specific focal dystonia (TSFD), characterized by the loss of fine motor control and coordination, affects drummers’ lower-limb movements. This study explores lower-limb dystonia’s impact on drumming performance and underlying muscle activity in a professional rock drummer. The drummer executed an eight-beat pattern on a drum kit. The participant reported the occurrence of symptoms when he felt the abnormality such as the loss of control related to involuntary aspects of movement. We measured the peak amplitude of the bass drumhead vibration, synchronization errors as the time elapsed between the metronome onset and the bass drum onset, and amplitude of electromyographic (EMG) recordings centered on metronome beat. Dystonia symptoms primarily manifested in the initial beat, with fewer symptoms on syncopation of the third beat. Analysis revealed decreased bass-drum peak amplitude and earlier synchronization error during the initial beat. EMG measurements of 10 muscles in the affected right lower limb showed significant changes in the Biceps Femoris (BF), Tibialis Anterior (TA), Extensor Digitorum Longus (EDL), and Extensor Digitorum Brevis (EDB) muscles during symptom onset. We observed (1) earlier overactivation of the TA and EDL muscles during the leg lift-up motion or preparatory phase of pedaling, (2) reduced activation of the EDB muscle, and (3) increased activation of the BF muscle during the final pedaling movement when symptoms occurred. These findings suggest that lower-limb dystonia symptoms are characterized by a reduction in amplitude of the bass drumhead vibration and an increase in synchronization error, potentially due to premature overactivation of the ankle dorsiflexor muscles.